User Centered Design Method for Designing a Student Organization Information System at the University of Al Azhar Indonesia - Hidayati, Nurul Aulia; Haryadi, Dody (Universitas Al Azhar Indonesia, 2024)
University of Al Azhar Indonesia has 39 student organizations that serve as a forum for student development in various fields, both academic and non-academic. Currently, in the administration and documentation of student organization activities, they still use Google Form, Google Drive, and Google Sheets. The use of these platforms creates a major problem when submitting activity proposals, as there is no submission history that can result in duplicate submissions and affect the review time by the Student and Alumni Council. This research aims to develop a web-based information system that can facilitate student organization administrators and activity reviewers in carrying out UAI student organization administration. The development of this system adopts the User Centered Design (UCD) method, a design approach that focuses on user needs so that the end result of the application does not change user behavior. The UCD method consists of four stages, namely planning human-centered design, determining user and organizational needs, designing product solutions, and evaluating designs based on user needs.